Konsep Diri Individu Pengguna Media Sosial - Wimona, Stephanie; Loisa, Riris (Koneksi, 2022)
Social media has evolved into the most frequently used platform for obtaining up-to-date information and has evolved into the trend-setting platform for everyday people. The researchers in this study focused on Instagram, one of the most popular social media platforms among teenagers, particularly students. Researchers examined Instagram's impact as a daily social media platform used by students. According to the findings, Instagram influences an individual's mindset, which in turn influences the individual's perception of his or her own concept. Individuals engage in intrapersonal communication following the acquisition of information, according to self-disclosure theory. Individuals in this position use intrapersonal communication to form judgments and perceptions about themselves, both positive and negative. Intrapersonal communication benefits individuals and can become self-motivating when individuals are experiencing difficulties. Media sosial sudah menjadi platform yang paling sering digunakan untuk mengambil informasi terbaru dan menjadi trend-setter masyarakat sehari-hari. Dalam penelitian ini, peneliti melakukan riset terhadap Instagram sebagai salah satu media sosial yang paling sering digunakan oleh remaja khususnya kalangan mahasiswa. Peneliti menganalisis efek pengaruh dari Instagram sebagai media sosial yang dikonsumsi oleh mahasiswa setiap harinya. Dari hasil temuan, dapat disimpulkan bahwa Instagram mempengaruhi pola pikir individu yang nantinya akan mempengaruhi persepsi individu terhadap konsep dirinya sendiri. Dengan menggunakan teori pengungkapan diri (self-disclosure), individu cenderung melakukan komunikasi intrapersonal setelah menyerap informasi. Komunikasi intrapersonal di posisi ini menjadi sarana individu dalam menarik kesimpulan dan persepsi yang baik maupun buruk terhadap dirinya sendiri. Dalam halnya pemanfaatan, komunikasi intrapersonal membantu individu dan mampu menjadi motivasi diri saat individu sedang terpuruk dalam suatu masalah.